2017
DOI: 10.1038/srep44809
|View full text |Cite
|
Sign up to set email alerts
|

BAP31 is involved in T cell activation through TCR signal pathways

Abstract: BAP31 is a ubiquitously expressed endoplasmic reticulum (ER) membrane protein. The functions of BAP31 in the immune system have not been investigated due to the lack of animal models. Therefore we created a BAP31 conditional knockdown mouse by performing a knockdown of BAP31 in the thymus. In doing so, we demonstrate that the maturation of T cells is normal but the number of T cells is less in the thymus of the knockout mouse. In addition, the spleen and lymph nodes of peripheral immune organs contained a less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Our previous study reported that BAP31 associates with the N terminus of the CFTRΔF508 and promotes its retro‐translocation from the ER and its degradation by the cytoplasmic 26S proteasome system . In addition, our recent studies clarified that BAP31 is also involved in T cell activation, hepatic lipid accumulation and insulin resistance …”
Section: Introductionmentioning
confidence: 97%
“…Our previous study reported that BAP31 associates with the N terminus of the CFTRΔF508 and promotes its retro‐translocation from the ER and its degradation by the cytoplasmic 26S proteasome system . In addition, our recent studies clarified that BAP31 is also involved in T cell activation, hepatic lipid accumulation and insulin resistance …”
Section: Introductionmentioning
confidence: 97%
“…Details on the targeting construct and targeting procedure were reported in our previous study (14, 15). Mice with the BAP31 flox allele (BAP31 flox/− ) on the C57BL/6 background were mated with the transgenic mice expressing Cre recombinase under the control of calcium/calmodulin‐dependent protein kinase type II α chain promoter (Camk2a‐Cre mice) to obtain hemizygous Camk2a‐Cre‐BAP31 flox/− offspring.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study reported that BAP31 interacted with Sec61 translocons and promoted the retrotranslocation of the CFTR mutant CFTRDF508 to its proteasome degradation pathway (13). Furthermore, our group reported that BAP31 is involved in T cell activation (14), hepatic lipid accumulation, and insulin resistance (15). BAP31 itself is a preferred substrate of caspase‐8, and its cleavage contributes directly to apoptosis progression.…”
mentioning
confidence: 99%
“…S4A). It has been shown that CFTR∆F508 that escapes from degradation by the ERAD pathway can reach the cell membrane [4], therefore, we assessed CFTR∆F508 expression on the cell surface. The results of the flow cytometry analysis showed that more CFTR∆F508 reached the cell surface after 2 hrs of treatment with DBeQ (2.5 μM) (Fig.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…For the Western blot analysis of protein expression, the cells were resuspended in RIPA buffer [4] at 4 °C for 30 min and then centrifuged at 12, 000 rpm for 15 min. Then, 5× sodium dodecyl sulfate (SDS) sample buffer was added to the supernatant, and the sample was boiled.…”
Section: Western Blotmentioning
confidence: 99%